2015
DOI: 10.2174/1389450116666150825111439
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Novel Targets for Treatment of Liver Fibrosis: What Can We Learn from Injured Tissues which Heal Without a Scar?

Abstract: The liver is unique in that it is able to regenerate. This regeneration occurs without formation of a scar in the case of non-iterative hepatic injury. However, when the liver is exposed to chronic liver injury, the purely regenerative process fails and excessive extracellular matrix proteins are deposited in place of normal liver parenchyma. While much has been discovered in the past three decades, insights into fibrotic mechanisms have not yet lead to effective therapies; liver transplant remains the only cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 213 publications
(249 reference statements)
1
13
0
Order By: Relevance
“…This glycoprotein has been identified to modulate the structural environment of regeneratively healing fetal skin and adult liver wounds (16,32). Similar to the results found in MRL/MpJ, early increases in HA in the peri-cellular and extra-cellular space during early fetal healing modulates the cell–matrix relationship, and can increase availability and efficiency of receptor-ligand interactions necessary to modulate cell behavior and induce regeneration (15,16,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This glycoprotein has been identified to modulate the structural environment of regeneratively healing fetal skin and adult liver wounds (16,32). Similar to the results found in MRL/MpJ, early increases in HA in the peri-cellular and extra-cellular space during early fetal healing modulates the cell–matrix relationship, and can increase availability and efficiency of receptor-ligand interactions necessary to modulate cell behavior and induce regeneration (15,16,32).…”
Section: Discussionmentioning
confidence: 99%
“…This glycoprotein has been identified to modulate the structural environment of regeneratively healing fetal skin and adult liver wounds (16,32). Similar to the results found in MRL/MpJ, early increases in HA in the peri-cellular and extra-cellular space during early fetal healing modulates the cell–matrix relationship, and can increase availability and efficiency of receptor-ligand interactions necessary to modulate cell behavior and induce regeneration (15,16,32). In adulthood, however, prolonged increases in HA, similar to what is seen in scar-mediated healing C57Bl/6 tendons at 4-week post-injury, have been implicated in lung, liver, and kidney fibrosis labeling this glycoprotein as a marker for disease progression (3335).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of NAFLD progression have found that the severity of liver fibrosis is the only feature of NASH that independently predicts liver-related morbidity and mortality 11 . Further research is needed to determine why progressive scarring develops in only some patients with NASH, define the mechanisms that shift effective regeneration to pathologic scarring 42,43 , and determine how wound-healing responses might be modulated to heal lipotoxicity without scar 44 .…”
Section: Pathogenesismentioning
confidence: 99%
“…Other growth factors such as growth factor derived from platelets (PDGF) and fibroblast growth factor (FGF) also exhibit temporal and spatial differences in fetal wound healing [32]. Exogenous PDGF (mitogen and chemotactic factor for fibroblasts) induces fibrosis in fetal wounds in rabbits [33].…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%